2020
DOI: 10.1186/s12889-020-09452-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of kitchens sponges used in university student dormitories

Abstract: Background Kitchen sponges are a major source of cross-contamination as they can transfer foodborne pathogens, infectious agents and spoilage causing microorganisms to food contact surfaces. Several studies have revealed that university students adopt poor practices regarding food safety, hygiene, and the handling of kitchen cleaning equipment. Methods A total of fifty kitchen sponges were collected along with a questionnaire addressing social demographics and kitchen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
1
17
1
1
Order By: Relevance
“…A higher percentage of our participants have insufficient knowledge on the proper use of reusable kitchen sponges as they reported using them for multiple purposes such as dishes and sink. This finding contrasts with a previous study that showed that a high percentage (74%) of female students in university dormitories used different sponges for cleaning utensils and the sink (26).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A higher percentage of our participants have insufficient knowledge on the proper use of reusable kitchen sponges as they reported using them for multiple purposes such as dishes and sink. This finding contrasts with a previous study that showed that a high percentage (74%) of female students in university dormitories used different sponges for cleaning utensils and the sink (26).…”
Section: Discussioncontrasting
confidence: 99%
“…The questionnaire was designed by adapting some existing questions from validated and reliable questionnaires used in prior studies pertaining to food safety (10,16,(20)(21)(22)(23)(24)(25)(26)(27)(28). All authors went through the questionnaire in-tandem to discuss the questions that need to be included in the study.…”
Section: Questionnairementioning
confidence: 99%
“…To avoid foodborne illnesses, the kitchen sink must be cleaned with hot water, soap, and then a disinfectant after every use [8,31]. The kitchen sponges need to be changed on a regular basis as they could act as a vehicle for cross-contamination [32]. Unclean kitchen sponges have been reported to contain a high number of pathogenic bacteria such as Campylobacter spp., Enterobacter cloacae, E. coli, Klebsiella spp., Proteus spp., Salmonella spp., Acinetobacter, Moraxella, and Staphylococcus spp.…”
Section: Personal Hygiene and Cleaningmentioning
confidence: 99%
“…Unclean kitchen sponges have been reported to contain a high number of pathogenic bacteria such as Campylobacter spp., Enterobacter cloacae, E. coli, Klebsiella spp., Proteus spp., Salmonella spp., Acinetobacter, Moraxella, and Staphylococcus spp. [32]. A study conducted on Lebanese food handlers showed that 86.8% of them washed the kitchen sink with hot water, soap, and then a disinfectant [33].…”
Section: Personal Hygiene and Cleaningmentioning
confidence: 99%
“…Other studies reported potentially pathogenic bacteria in kitchen sponges, too, such as Klebsiella spp. (Adiga et al 2012 ; Marshall et al 2012 ; Osaili et al 2020 ), Escherichia coli (Adiga et al 2012 ; Marshall et al 2012 ), or Salmonella spp. (Rossi et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%